Security and Geopolitical Concerns in the Middle East after the Martyrdom of Ismail Haniyeh: the Political Leader of Hamas - Ibrahimi, Mohammad Reza (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
This paper aims to analyze the conflict between Palestine and Israel, particularly following the martyrdom of Hamas leader Ismail Haniyeh. The transition in leadership within Hamas may lead to significant strategic shifts in the group's operations. Employing a qualitative approach and a literature review method, this research will explore relevant literature and incorporate geopolitical perspectives to assess the impact of Ismail Haniyeh's martyrdom on Middle Eastern security and its implications for regional and international stability. Despite the International Court of Justice (ICJ) instructing Israel to prevent genocide against Palestinian civilians and address the humanitarian crisis in the Gaza Strip, Israel continues to carry out attacks and killings in densely populated areas. International pressure, including from the United Nations, appears ineffective in curbing Israel's military aggression. Israel's inhumane treatment of Palestinians is not a new issue but has been a recurring problem. Therefore, given the aforementioned facts and realities, it is appropriate for countries around the world, including Iran, to adopt a firmer stance against Israel's arrogance and brutality towards Palestinian sovereignty and the geopolitical security of the Middle East.